Tinjauan Yuridis terhadap Sistem Pembelian Properti di Indonesia Studi Kasus: PT Agung Sedayu Group - Elisabeth Niuflapu; Wilma Silalahi (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to examine the legal aspects of the property purchase system in Indonesia with a focus on the practices implemented by PT Agung Sedayu Group as one of the leading property developers. The property purchase system in Indonesia still faces various legal challenges, ranging from legal certainty of land rights, legality of sale and purchase agreements, to consumer protection. Through a normative legal approach and case studies, this study analyzes applicable regulations such as Law Number 5 of 1960 concerning Basic Agrarian Principles, the Consumer Protection Law, and implementing regulations related to licensing and property sale and purchase transactions. The results of the general study indicate that although in general PT Agung Sedayu Group has complied with applicable legal provisions, there are still several aspects that need to be improved, especially related to transparency of information to consumers and the mechanism for resolving settlements. This study encourages enforcement of regulations and supervision of developers and increasing consumer legal awareness in property transactions.